Pengaruh Model Pembelajaran Make a Match terhadap Pemahaman Kosakata Bahasa Inggris di Sekolah Dasar - Wangsa, Aisyah Nina; Ruswan, Acep; Nurmahanani, Indah (AS-SABIQUN, 2023)
The ability to speak English is one of the most important skills in the digital era like now. Therefore it is very important to start learning English as early as possible. But in fact the ability to understand English among students is still relatively low, this is in line with what Patrius said that learning English is not as easy as learning the latest series of gadgets. This research was conducted with the aim of: 1) Knowing the ability to understand students' English vocabulary before applying the learning make a match;2) Knowing the ability to understand students' English vocabulary after applying the learning make a match; 3) The influence of learning make a match on students' English vocabulary understanding ability. The research method used in this research is pre-experimental one group pretest – posttest design. The research sample is 20 IC class students at one of the schools in Purwakarta. An English vocabulary comprehension test instrument was used to obtain data before and after treatment. The research results show that there is an influence of the learning to make a match on the understanding of English vocabulary, this can be seen from the results of the T test with T count > T table so that Ho is accepted which means there is a significant difference. The results of a simple linear regression test with an R-Square of 0.748 or 74.8%. There is an increase in the ability to understand English vocabulary by looking at the average value N-Gain of 0.62 in the moderate category.